Significance of Cytomegalovirus gB Genotypes in Adult Patients Undergoing Hematopoietic Stem Cell Transplantation: Insights from a Single-Centre Investigation - Tamara Vasiljevic; Marko Jankovic; Ana Tomic; Ida Bakrac; Stefan Radenovic; Danijela Miljanovic; Aleksandra Knezevic; Tanja Jovanovic; Irena Djunic; Milena Todorovic-Balint (MDPI AG, 2024)
Introduction: Cytomegalovirus (CMV) infection is a major clinical issue after allogeneic hematopoietic stem cell transplantation (HSCT). The CMV envelope glycoproteins are key in viral pathogenesis; the glycoprotein B (gB) encoded by the UL55 gene might be an important determinant of viral virulence and disease severity marker in patients treated with allogeneic HSCT. Our aim was to investigate the molecular diversity of CMV gB and inquire into the associations between UL55 gene variations and clinical manifestations in adult patients treated with allogeneic HSCT. Results: The most prevalent genotypes were gB1 and gB4 (11/27, 40.7%). Patients with genotype gB1 infection had earlier platelet engraftment (p < 0.033) and less frequent minimal/measurable residual disease post HSCT than those without this genotype. Patients with gB4 glycoprotein infection had a significantly lower CD4+/CD8+ ratio at D90 (p < 0.026). Interestingly, patients with gB5 glycoprotein infection had shorter overall survival from base condition diagnosis (p < 0.042), as well as shorter overall survival after HSCT (p < 0.036). Acute GvHD was noted more frequently in those with mixed-genotype infection (p = 0.047). Material and Methods: The study included fifty-nine adult patients treated with allogeneic HSCT. Peripheral venous blood was sampled typically per week, with detection of CMV performed by quantitative real-time PCR. Multiplex nested PCR was used to determine specific gB genotypes, which were then statistically compared vis-à-vis specific clinical variables. Conclusions: Our study points to variations in the viral UL55 locus imparting both beneficial (earlier platelet engraftment, less frequent MRD post HSCT) and adverse effects (shorter overall survival, more frequent acute GvHD, less frequent 100% chimerism at day 90) to the transplanted host. Comprehensive molecular investigations are necessary to validate this apparent duality, as the potential benefits of CMV could perhaps be utilized for the benefit of the patient in the future.